2010
DOI: 10.1371/journal.pone.0011868
|View full text |Cite
|
Sign up to set email alerts
|

Axons Amplify Somatic Incomplete Spikes into Uniform Amplitudes in Mouse Cortical Pyramidal Neurons

Abstract: BackgroundAction potentials are the essential unit of neuronal encoding. Somatic sequential spikes in the central nervous system appear various in amplitudes. To be effective neuronal codes, these spikes should be propagated to axonal terminals where they activate the synapses and drive postsynaptic neurons. It remains unclear whether these effective neuronal codes are based on spike timing orders and/or amplitudes.Methodology/Principal FindingsWe investigated this fundamental issue by simultaneously recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…Similar results have been obtained in neurons of the subthalamic nucleus [42] and granule cells in the dentate gyrus [43] . Dual recordings from the soma and axon also indicated that cortical and subcortical axons faithfully propagate action potentials [2,42,44] , even at high firing frequencies (up to 400 Hz) [40] and during epileptiform activity [2] .…”
Section: Unlike Cerebellar Purkinje Cells Layer-5 Pyramidal Neuronsmentioning
confidence: 94%
“…Similar results have been obtained in neurons of the subthalamic nucleus [42] and granule cells in the dentate gyrus [43] . Dual recordings from the soma and axon also indicated that cortical and subcortical axons faithfully propagate action potentials [2,42,44] , even at high firing frequencies (up to 400 Hz) [40] and during epileptiform activity [2] .…”
Section: Unlike Cerebellar Purkinje Cells Layer-5 Pyramidal Neuronsmentioning
confidence: 94%
“…ARPs were measured by injecting paired-depolarization pulses (3 ms) into these neurons after each spike. By changing interpulse intervals, we defined ARPs as the time from a complete spike to its subsequent spike at 50% probability [59, 60]. …”
Section: Methodsmentioning
confidence: 99%
“…The identification of axonal blebs rather than dendritical bleb was based on the diameter and branches of processes as well as the polarity of neurons [13,15]. Neuronal processes with less branches and fine diameter are axon.…”
Section: Methodsmentioning
confidence: 99%